Prespektif Komisi Pemberantasan Korupsi Dalam Tinjauan Hukum Tata Negara Islam - Aidil Ihsan; Sa’adatul Maghfira (Politik Islam, 2023)
The main problem in this journal is how the Corruption Eradication Agency in Islamic State Administrative Law. The purpose of this discussion is to identify and describe the Corruption Eradication Agency in Islamic State Administrative Law and to analyze how Islamic state constitutional law is reviewed. The research method used in this thesis is the library research method, which is a research carried out by reading literature books that have a relationship with the problems studied regarding Corruption Eradication Institutions in Islamic Constitutional Law. This research is descriptive-analytic in nature, that is, the analysis only reaches the description stage. This research can be categorized as the type of research that the author does is library research, which is related to Corruption Eradication Institutions viewed from the perspective of Islamic Constitutional Law. This research is qualitative with the Normative Method. The normative approach is that this approach is carried out by approaching the problem from a legal perspective, discussing, and reviewing existing books and statutory provisions related to the Corruption Eradication Agency according to the perspective of Islamic constitutional law. From the results of the research conducted by the author, it can be concluded that, according to the view of Islamic Constitutional Law, the existence of a corruption eradication institution is permissible (mubah) as long as the corruption eradication institution provides the benefit of the people. The Islamic Constitutional Law itself does not find precise references to independent institutions such as corruption eradication agencies, but in essence the duties and powers of the Mazhalim Region are almost similar to the Corruption Eradication Agency. The Mazhalim region is an institution which is a power in the field of justice that is higher than the Judge and Mah'tasb.